Formulating the Relationship of Mean Kicking Angle and Leg Flexibility Index for Silat Athletes Using Regression Analysis - Nurul Afiqah Ibrahim; Jumadi, Nur Anida (Evolution in Electrical and Electronic Engineering, 2021)
Silat is one of the martial arts involving various techniques of kicking which its utilization can be related to one’s flexibility. In this research paper, it is assumed that the greater the kicking angle, the greater will be the leg flexibility index. Based on this assumption, several objectives have been formulated which are first; to modify the existing flexibility index formula to suit with the current needs, to formulate linear equations based on regression analysis and finally to analyze the developed formula based on residual plot analysis. Twenty participants from two different backgrounds; silat athlete (n=10) and non-athletes (n=10) were recruited to perform three trials of kicking in order to obtain their average kicking angle whereas their leg flexibility index were calculated using the proposed modified formula. Both of these parameters were used as the inputs for finding the relationship between mean kicking angle and leg flexibility index in the form of linear equation. The regression analysis was performed using Excel and the main findings revealed the accuracy based on R2 value were above 0.9 for both models with residual values were approximate to zero, indicated high quality of relationship equation models generated from the silat and non-silat athletes. Future works will include the validation experiment using sit and reach test for evaluating the performance of the obtained models as well as machine learning implementation using Matlab for producing prediction models.